Emerging Multinationals from Mid‐Range Economies: The Influence of Institutions and Factor Markets. (28th December 2012) - Hoskisson, Robert E.; Wright, Mike; Filatotchev, Igor; Peng, Mike W.
Abstract This paper revisits and extends our earlier work (in 2005) in the pages of this journal. We argue that there is a need for more fine‐grained understanding of the country context along two dimensions: (1) institutional development and (2) infrastructure and factor market development. Specifically, we propose an enriched typology of emerging economies with a focus on mid‐range emerging economies, which are positioned between traditional emerging economies and newly developed economies. Then we examine new multinationals from these mid‐range emerging economies that have internationalized both regionally and globally. We outline directions for further research based on this typology in terms of (1) government influence, (2) resource orchestration, (3) market entry, and (4) corporate governance regarding the internationalization strategy of these emerging multinationals from mid‐range economies.